Assessing the Communication Skills of Medical Students: Bridging the Gap in Patient Centred Care - Aruna Davis; Biju Bahuleyan (GAIMS Journal of Medical Sciences, 2023)
Background: Effective communication is essential for quality healthcare delivery. However, communication skills training is often overlooked in medical education, leading to inadequate skills among young doctors and compromised patient care. This study aimed to assess the communication skills of first-year medical students and analyse their attitudes towards the importance of communication skills.